Microbial quality and yeast population dynamics in cracked green table olives' fermentations - Alves, Maria (2012)
Cracked green table olives, from the Manzanilla variety, are a fermented food produced and consumed in Portugal. The objective of the present work was to study the microbiological characteristics and yeast population evolution during the fermentation of cracked green olives. The predominant microorganisms were yeasts while lactic acid bacteria were not detected and a clear decrease of the mould population was observed. At the end of the fermentations, no viable counts of Enterobacteriaceae were found. Yeast isolates were identified by the 5.8S rRNA-ITS region restriction analysis and by sequencing the D1/D2 region of the 26S rRNA gene. During the initial phases of the fermentations a great diversity of yeasts was observed. However, as the processes evolved the biodiversity decreased with the fermentative yeasts Citeromyces matritensis, Zygotorulaspora mrakii and Saccharomyces cerevisiae becoming the dominant species. The presence of these fermentative yeasts at the end of the production process is associated to a risk of spoilage. The results obtained represent a first attempt towards the comprehension of the microbiota of this type of “Natural olives” that constitute an important component of the Mediterranean diet.